The role of supervision in resistance training; an exploratory systematic review and meta-analysis - Fisher, J. P.; Steele, J.; Wolf, M.; Androulakis Korakakis, P.; Smith, D.; Giessing, J. (International Journal of Strength and Conditioning, 2022)
Background: Since many people choose to perform resistance training unsupervised, and a lack of supervision within strength training is reported to result in inadequate workout quality, we aimed to compare outcomes for resistance training with and without supervision. Methods: A systematic review and meta-analysis were performed for performance/functional outcomes and/or body composition measurements. Results: 12 studies were included in the review; 301 and 276 participants were in supervised and unsupervised groups, respectively. The main model for all performance/function effects revealed a small, standardised point estimate favouring SUP (0.28 [95%CI = 0.02 to 0.55]). For sub-grouped outcome types, there was very poor precision of robust estimates for speed, power, function, and endurance. However, for strength there was a moderate effect favouring SUP (0.40 [95%CI = 0.06 to 0.74]). The main model for all body composition effects revealed a trivial standardised point estimate favouring SUP (0.07 [95%CI = -0.01 to 0.15]). Conclusions: Supervised resistance training, compared to unsupervised training, might produce a small effect on increases in performance/function, most likely in strength, but has little impact on body composition outcomes